Experimental validation of model‐based blade pitch controller design for floating wind turbines: system identification approach. Issue 7 (6th February 2017) - Hara, N.; Tsujimoto, S.; Nihei, Y.; Iijima, K.; Konishi, K.
Abstract: This paper discusses the model‐based design of a blade pitch controller for a floating offshore wind turbine (FOWT) scale model. A mathematical model of the FOWT is constructed from an input–output measurement in an experiment using system identification. The blade pitch controller is designed by an H ∞ control method, and the effectiveness of the controller is evaluated by means of a basin experiment using the FOWT scale model. The results show that the blade pitch controller is effective in reducing platform pitch motion and rotor speed fluctuation. Copyright © 2017 John Wiley & Sons, Ltd.